Solution of an equation involving a single variable

Algebra Level 2

Solve the following equation for x x :

2 x 3 + 5 x 1 = 3 x 2 \sqrt {2x-3}+\sqrt {5x-1}=\sqrt {3x-2}

If you think that no solution exists, then give the input as 0


The answer is 0.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

3 solutions

Gandoff Tan
Oct 21, 2019

2 x 3 + 5 x 1 = 3 x 2 5 x 1 = 3 x 2 2 x 3 5 x 1 = ( 3 x 2 ) 2 ( 3 x 2 ) ( 2 x 3 ) + ( 2 x 3 ) 4 = 2 ( 3 x 2 ) ( 2 x 3 ) 2 = 6 x 2 13 x + 6 6 x 2 13 x + 6 = 4 6 x 2 13 x + 2 = 0 ( x 2 ) ( 6 x 1 ) = 0 x = 2 (rej.) or x = 1 6 (rej.) no solution. \begin{aligned} \sqrt{2x-3}+\sqrt{5x-1}&=\sqrt{3x-2}\\ \sqrt{5x-1}&=\sqrt{3x-2}-\sqrt{2x-3}\\ 5x-1&=(3x-2)-2(\sqrt{3x-2})(\sqrt{2x-3})+(2x-3)\\ 4&=-2\sqrt{(3x-2)(2x-3)}\\ -2&=\sqrt{6x^2-13x+6}\\ 6x^2-13x+6&=4\\ 6x^2-13x+2&=0\\ (x-2)(6x-1)&=0\\ x&=2\text{ (rej.) or }x=\frac16\text{ (rej.)}\\ \therefore\boxed{\text{no solution.}} \end{aligned}

Chris Lewis
Oct 21, 2019

It's tempting to square both sides immediately, but rearranging first leads to some helpful cancellation:

5 x 1 = 3 x 2 2 x 3 \sqrt{5x-1}=\sqrt{3x-2}-\sqrt{2x-3}

Squaring:

5 x 1 = 3 x 2 2 3 x 2 2 x 3 + 2 x 3 = 5 x 5 2 3 x 2 2 x 3 5x-1=3x-2-2\sqrt{3x-2} \cdot \sqrt{2x-3} + 2x-3=5x-5-2\sqrt{3x-2} \cdot \sqrt{2x-3}

Cancelling and rearranging again:

4 = 2 3 x 2 2 x 3 4=-2\sqrt{3x-2} \cdot \sqrt{2x-3}

Dividing through by 2 2 and squaring again:

4 = ( 3 x 2 ) ( 2 x 3 ) 4=(3x-2)(2x-3)

This is just a quadratic; expanding and rearranging we have 6 x 2 13 x + 2 = 0 6x^2-13x+2=0 , with roots x = 1 6 x=\frac16 and x = 2 x=2 .

Note the order of the logic above: we've shown that if x x is a root of the original equation, it must be either 1 6 \frac16 or 2 2 . This doesn't mean that these are roots; we need to check by substituting back in to the original equation, and we find neither of these values works. Since the above chain of reasoning showed that these were the only two possibilities we had to check, we can conclude that the equation has no roots .

After so many days you are back! You can ascertain that the equation has no solution from the step 4 = 2 3 x 2 . 2 x 3 4=-2\sqrt {3x-2}.\sqrt {2x-3} , because you are equating a positive number with a negative one, and a positive number can never be equal to a negative one.

A Former Brilliant Member - 1 year, 7 months ago
Callie Ferguson
Oct 20, 2019

( A + B ) 2 = C 2 (A+B)^2 = C^2

Where A = ( 2 x 3 ) A = \sqrt(2x-3) , B = ( 5 x 1 ) B = \sqrt(5x-1) , and C = ( 3 x 2 ) C = \sqrt(3x-2)

First, square both sides of the equation. To square the lefthand side, see below. Do not simply remove the radicals from each term.

( A + B ) ( A + B ) = A 2 + 2 A B + B 2 (A+B)(A+B) = A^2 + 2AB + B^2

{ A 2 = 2 x + 3 B 2 = 5 x 1 A B = 10 x 2 2 x + 15 x 3 = 10 x 2 + 13 x 3 C 2 = 3 x 2 \begin{cases} A^2 & = 2x+3 \\ B^2 & = 5x-1 \\ AB & = 10x^2-2x+15x-3 = 10x^2+13x-3 \\ C^2 & = 3x-2 \end{cases}

So, squaring both sides of the equation gives:

( 2 x + 3 ) + 2 ( 10 x 2 2 x + 15 x 3 = 10 x 2 + 13 x 3 ) + ( 5 x 1 ) = 3 x 2 (2x + 3) + 2\sqrt(10x^2-2x+15x-3 = 10x^2+13x-3) + (5x - 1) = 3x - 2

Simplified:

2 x 2 = ( 10 x 2 + 13 x 3 = 10 x 2 + 13 x 3 ) -2x-2 = \sqrt(10x^2+13x-3 = 10x^2+13x-3)

0 = 6 x 2 + 5 x 7 0 = 6x^2+5x-7

This does not give an integer value for x, so the equation does not have a rational solution (input "0").

What about the irrational roots? Moreover, no integer solution is asked for. Also, how comes A 2 = 2 x + 3 A^2=2x+3 ?

A Former Brilliant Member - 1 year, 7 months ago

Log in to reply

I meant 2x-3, sorry! And I tried answering with the irrational roots but it told me the answer had to be an integer

Callie Ferguson - 1 year, 7 months ago

Log in to reply

Check for the equation A B = 10 x 2 + 13 x 3 AB=10x^2+13x-3 , this is also wrong.

A Former Brilliant Member - 1 year, 7 months ago

Log in to reply

@A Former Brilliant Member are you sure? what is it?

Callie Ferguson - 1 year, 7 months ago

Log in to reply

@Callie Ferguson Now comes the point. Your A B AB is 2 x 3 × 5 x 1 = 10 x 2 17 x + 3 \sqrt {2x-3}\times \sqrt {5x-1}=\sqrt {10x^2-17x+3} . Manipulation doesn't always lead to success.

A Former Brilliant Member - 1 year, 7 months ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...